TINJAUAN HISTORIS PENYUSUNAN RERANGKA KONSEPTUAL - Kustono, Alwan Sri (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
An accounting conceptual framework can be defined a coherent system of inter-related objectives and fundamentals that should lead to consistent standards that prescribe the nature, function and limits of financial accounting and financial statements.The main reasons for developing an agreed conceptual framework are that it providesa framework for setting accounting standards, a basis for resolving accounting disputes, and fundamental principles which then do not have to be repeated in accounting standards. This article has outlined the history and nature of a accounting conceptual framework. The article showed this important area which is fundamental to understanding the whole process of developing accounting standards. Key words: conceptual framwork, FASB, IASC, IFRS